2010
DOI: 10.1136/gut.2008.174599
|View full text |Cite
|
Sign up to set email alerts
|

Use of endoscopy for management of acute upper gastrointestinal bleeding in the UK: results of a nationwide audit

Abstract: Objectives To examine the use of endoscopy in the UK for acute upper gastrointestinal bleeding (AUGIB) and compare with published standards. To assess the organisation of endoscopy services for AUGIB in the UK. To examine the relationship between outcomes and out of hours (OOH) service provision. Design Multi-centre cross sectional clinical audit. Setting All UK hospitals accepting admissions with AUGIB. Patients All adults ($16 yrs) presenting with AUGIB between 1st May and 30th June 2007. Data Collection A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
152
3
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(173 citation statements)
references
References 23 publications
9
152
3
9
Order By: Relevance
“…Current evidence sug- gests that early administration of PPIs is the standard treatment of patients with NVUGB (20)(21)(22)(23)(24). The rebleeding rate observed in our patients (3.4%) was similar to that observed in the Italian PNED study (3.2%) and in other recent publications (17,18), but it was significantly lower than that reported in the Canadian RUGBE study (14.1%) (3,5,8). The divergence of our results from the ones of the Canadian study may be explained because a higher proportion of our patients received combined endoscopic therapy (adrenaline injection plus BICAP) than in the Canadian study; combined therapy has been shown to be superior to pharmacologic treatment for reduction of rebleeding in controlled trials (25)(26)(27).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Current evidence sug- gests that early administration of PPIs is the standard treatment of patients with NVUGB (20)(21)(22)(23)(24). The rebleeding rate observed in our patients (3.4%) was similar to that observed in the Italian PNED study (3.2%) and in other recent publications (17,18), but it was significantly lower than that reported in the Canadian RUGBE study (14.1%) (3,5,8). The divergence of our results from the ones of the Canadian study may be explained because a higher proportion of our patients received combined endoscopic therapy (adrenaline injection plus BICAP) than in the Canadian study; combined therapy has been shown to be superior to pharmacologic treatment for reduction of rebleeding in controlled trials (25)(26)(27).…”
Section: Discussionsupporting
confidence: 92%
“…In our study the occurrence of clinical manifestations of bleeding, the frequency of non-ulcerative lesions, the severity of gastrointestinal bleeding and the frequency of endoscopic high-risk stigmata for rebleeding were similar to those reported in the literature (11,(17)(18)(19). Nevertheless, the use of PPIs was not found as a protector risk factor of death in contrast to that observed in other studies.…”
Section: Discussionsupporting
confidence: 88%
“…[12][13][14] Only half of DGHs offer an acute gastrointestinal bleed service, which reflects the findings of other surveys. 15,16 A recent study showed that no change in mortality is achieved with an emergency gastrointestinal bleed service. 15 Most hospitals use banding and sclerotherapy and administer terlipressin.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 A recent study showed that no change in mortality is achieved with an emergency gastrointestinal bleed service. 15 Most hospitals use banding and sclerotherapy and administer terlipressin. The use of antibiotic prophylaxis has been shown to reduce mortality in variceal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Upper gastrointestinal bleeding is an important cause of mortality worldwide (1)(2)(3)(4). Peptic ulcer disease is the most common cause of upper gastrointestinal bleeding (4)(5), and a significant proportion of peptic ulcers are caused by Helicobacter pylori (H. pylori) (6).…”
Section: Introductionmentioning
confidence: 99%